Desenvolvimento de filmes automontados baseados em compósitos de polipirrol e nanotubos de carbono para o monitoramento de pesticidas em ambiente marinho - Araujo, Gabriela Martins de [UNIFESP] (2017)
The development of sensor materials for the monitoring of endocrine disruptors substances such as pesticides, using electroanalytical methods like voltammetric techniques, have low cost and time analysis as advantages as well as offering the possibility of in-situ monitoring. Conducting polymers have as their main characteristic the electrical conductivity which can be regulated in a wide range, through interactions with acceptor and donors of electrons, which makes them attractive as transducers or active. Among the different conducting polymers the Polypyrrole is one of the most studied in the development of sensors. Already the carbon nanotubes have the ability to promote electron transfer reactions, increasing reaction speed and decreasing oxidation potentials. Thus, materials based on conducting polymer composites and carbon nanotubes have been developed and present synergistic properties like the increase of sensitivity and selectivity in relation to its separate materials. The aim of this work was to develop and characterize self-assembled films based on Polypyrrole and carbon nanotubes composites deposited on substrates of glass covered with indium-tin oxide and carbon screen-printed electrodes to monitor Diuron and Chlorothalonil pesticides which are commonly used in marine environment. The self-assembled films were characterized using the techniques of Cyclic Voltammetry, Electrochemical Impedance Spectroscopy, UV-Visible Spectroscopy and Scanning Electronic Microscopy. The applicability of the sensors was evaluated using the electroanalytical techniques of Square Wave Voltametry and Differential Pulse Voltammetry. The results showed the composite film on printed electrode substrate had more definite voltammetric peaks due to the synergism between the Polypyrrole and the carbon nanotubes resulting in an increase of the polymer currents, the reduction of the capacitive current and the decrease of the transfer resistance of load. The results of the applicability showed the composite film in printed electrode presented better sensitivity compared to the film of Polypyrrole due to the carbon nanotubes in their structure in the presence of the pesticide Diuron detecting this herbicide in oxidation potential of 0,58V being smaller than the potential already known in the literature that is around 1,1V. The LOQ and LOD were respectively 2,584. 10-6 mol.L-1 and 7,83.10-7 mol.L-1 for the analytical curve for the peak at 0,58V on the printed electrode made from the composite film.